Guía de Procedimientos Contables para las Empresas del Sector Hotelero obligadas a llevar Contabilidad de la Ciudad de Catamayo. - Uchuari Patiño, Jessica Jhuliana (2022)
The following Curriculum Integration Research entitled: GUIDE TO ACCOUNTING PROCEDURES FOR COMPANIES IN THE HOTEL SECTOR OBLIGED TO KEEP ACCOUNTING FROM THE CITY OF CATAMAYO, is focused on the publicizing and providing managers, owners, partners or shareholders of companies in the hotel sector, an instrument of support and guidance in the accounting field; promoting the proper development of each of the activities carried out and thus obtaining truthful and reliable information. To comply with the general objective set, a guide to accounting procedures was developed, which clearly establishes policies, procedures, formats of standard entries and flowcharts, which will facilitate the fulfillment of operations, make it possible to reduce errors and safeguard the resources obtained from the different sources of income and the control of expenditure. Its development was oriented in the development of accounting procedures since they are of great importance, they allow to have a record of transactions carried out daily; thus, it was started from establishing procedures related to cash such as: the opening of cash, tonnage of cash and closing of cash, followed by the process to follow the entry and the form of payment of the service, such as carrying out the acquisition of inputs and supplies to supply the different areas that hotel companies have, and the control of inputs and supplies that are used for daily consumption and use for the normal development of their activities, procedures related to tax matters specific to the sector were also determined, among other aspects those related to expenses and the presentation of economic reports were considered at the end of the period. Next, it was considered to establish accounting policies that would allow to streamline accounting processes, thus allowing them to execute, direct and control their activities, thus promoting the efficient performance of both economic and human resources that make up it; finally, the flowcharts of the processes were designed where you can graphically appreciate the activities to be carried out sequentially and those who intervene in them. Once the objectives have been met, it was concluded that this guide constitutes a valuable tool for accounting and financial management since compliance with procedures will contribute to obtaining detailed and orderly accounting information, as well as internal control, improving efficiency in tasks.